IMPLEMENTATION OF CLEAN ENERGY TECHNOLOGY SOLUTIONS AT AIRLANGGA COMMUNITY DEVELOPMENT HUB, GILI IYANG ISLAND, MADURA - Prisma Megantoro; Retna Apsari; Yoga Uta Nugraha; Marwan Fadhilah; Achmad Atho'illah Assakandary; Haikal Farabi; Muhammad Rafi Nabil Arsalan; Dimas Raka Buana Putra (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Gili Iyang is known as one of the areas with the best air quality in Indonesia. However, increased human activity has the potential to reduce air quality if not managed properly. Environmentally friendly technologies, such as electric vehicles, solar shelters, and air quality monitoring devices, are potential solutions to maintain the sustainability of clean energy in this area. This activity aims to increase public understanding of the importance of environmentally friendly technology, especially electric vehicles, solar shelters, and air quality monitoring, as well as promote the application of this technology in supporting ecotourism. The methods used include electric vehicle training for junior high school students and the installation of solar shelters and air concentration monitoring equipment at the Gili Iyang Assistant Health Center. This approach is designed to provide interactive education and practical solutions to the community. The activity showed a significant increase in junior high school students' understanding of electric vehicles, with 85% of participants understanding the working principles and benefits. Solar shelters can also be very useful in supporting the provision of electricity for residents. Thus, installing air concentration monitoring devices provides real-time information that helps the public and health workers make preventive decisions regarding potential air pollution. This activity increased public awareness about maintaining air quality and implementing environmentally friendly technology. In addition, implementing air monitoring tools contributes to the sustainability of ecotourism in Gili Iyang by combining technology and community-based education.